Patient Safety Culture in European Hospitals: A Comparative Mixed Methods Study - Granel-Giménez, Nina (2022)
“Background: Poorly organized health systems with inadequate leadership limit the development of the robust safety cultures capable of preventing consequential adverse events. Although safety culture has been studied in hospitals worldwide, the relationship between clinician perceptions about patient safety and their actual clinical practices has received little attention. Despite the need for mixed methods studies to achieve a deeper understanding of safety culture, there are few studies providing comparisons of hospitals in different countries. Purpose: This study compared the safety culture of hospitals from the perspective of nurses in four European countries, including Croatia, Hungary, Spain, and Sweden. Design: A comparative mixed methods study with a convergent parallel design. Methods: Data collection included a survey, participant interviews, and workplace observations. The sample was nurses working in the internal medicine, surgical, and emergency departments of two public hospitals from each country. Survey data (n = 538) was collected with the Hospital Survey on Patient Safety Culture (HSOPSC) and qualitative date was collected through 24 in-depth interviews and 147 h of non-participant observation. Survey data was analyzed descriptively and inferentially, and content analysis was used to analyze the qualitative data. Results: The overall perception of safety culture for most dimensions was ‘adequate’ in Sweden and ‘adequate’ to ‘poor’ in the other countries with inconsistencies identified between survey and qualitative data. Although teamwork within units was the most positive dimension across countries, the qualitative data did not consistently demonstrate support, respect, and teamwork as normative attributes in Croatia and Hungary. Staffing and workload were identified as major areas for improvement across countries, although the nurse-to-patient ratios were the highest in Sweden, followed by Spain, Hungary, and Croatia. Conclusions: Despite all countries being part of the European Union, most safety culture dimensions require improvement, with few measured as good, and most deemed to be adequate to poor. Dimension level perceptions were at times incongruent across countries, as observed patient safety practices or interview perspectives were inconsistent with a positive safety culture. Differences between countries may be related to national culture or variability in health system structures permitted by the prevailing European Union health policy.“